Population‐based birth defects data in the United States, 2012–2016: A focus on abdominal wall defects. Issue 18 (23rd October 2019) - Stallings, Erin B.; Isenburg, Jennifer L.; Short, Tyiesha D.; Heinke, Dominique; Kirby, Russell S.; Romitti, Paul A.; Canfield, Mark A.; O'Leary, Leslie A.; Liberman, Rebecca F.; Forestieri, Nina E.; Nembhard, Wendy N.; Sandidge, Theresa; et al.
Abstract: Background/Objectives: In this report, the National Birth Defects Prevention Network (NBDPN) examines and compares gastroschisis and omphalocele for a recent 5‐year birth cohort using data from 30 population‐based birth defect surveillance programs in the United States. Methods: As a special call for data for the 2019 NBDPN Annual Report, state programs reported expanded data on gastroschisis and omphalocele for birth years 2012–2016. We estimated the overall prevalence (per 10, 000 live births) and 95% confidence intervals (CI) for each defect as well as by maternal race/ethnicity, maternal age, infant sex, and case ascertainment methodology utilized by the program (active vs. passive). We also compared distribution of cases by maternal and infant factors and presence/absence of other birth defects. Results: The overall prevalence estimates (per 10, 000 live births) were 4.3 (95% CI: 4.1–4.4) for gastroschisis and 2.1 (95% CI: 2.0–2.2) for omphalocele. Gastroschisis was more frequent among young mothers (<25 years) and omphalocele more common among older mothers (>40 years). Mothers of infants with gastroschisis were more likely to be underweight/normal weight prior to pregnancy and mothers of infants with omphalocele more likely to be overweight/obese. Omphalocele was twice as likely as gastroschisis to co‐occur with other birth defects. Conclusions: This report highlights important differences between gastroschisis and omphalocele. These differences indicate the importance of distinguishing between these defects in epidemiologic assessments. The report also provides additional data on co‐occurrence of gastroschisis and omphalocele with other birth defects. This information can provide a basis for future research to better understand these defects.